Lipophilic pigments from the benthos of a perennially ice-covered Antarctic lake - Palmisano, A C (Hydrobiologia, 1989)
The benthos of a perennially ice-covered Antarctic lake, Lake Hoare, contained three distinct 'signatures' of lipophilic pigments. Cyanobacterial mats found in the moat at the periphery of the lake were dominated by the carotenoid myxoxanthophyll; carotenoids: chlorophyll a ratios in this high light environment ranged from 3 to 6.8. Chlorophyll c and fucoxanthin, pigments typical of golden-brown algae, were found at 10 to 20 m depths where the benthos is aerobic. Anaerobic benthic sediments at 20 to 30 m depths were characterized by a third pigment signature dominated by a carotenoid, tentatively identified as alloxanthin from planktonic cryptomonads, and by phaeophytin b from senescent green algae. Pigments were not found associated with alternating organic and sediment layers. As microzooplankton grazers are absent from this closed system and transformation rates are reduced at low temperatures, the benthos beneath the lake ice appears to contain a record of past phytoplankton blooms undergoing decay